Polytypism in GaAs/GaNAs core–shell nanowires. (7th October 2020) - Yukimune, M; Fujiwara, R; Mita, T; Ishikawa, F
Abstract: We report the crystal structures of GaAs and GaAs/GaNAs/GaAs core–multishell nanowires (NWs). From statistical investigations by x-ray diffraction (XRD) and electron backscattered diffraction (EBSD) pattern analysis, we statistically and microscopically resolve the zinc-blende (ZB) and wurtzite (WZ) polytypism within the NWs. The XRD analysis shows a smaller fraction of WZ segments in the NWs with a larger concentration of nitrogen. With increasing nitrogen content in the GaNAs shell, the ZB peak position shifts toward higher angles and the WZ peak intensity decreases. The EBSD measurements also confirm the coexistence of ZB and WZ polytypes in all of the NWs. Their polytype switches along the length. Twin defects are observed in the ZB segments in all of the NWs. The unique grain map and grain size distribution show a decrease of the WZ segments in the GaAs/GaNAs/GaAs NW, in agreement with the XRD results. Microscopically, the local area where the polytype switches from WZ in the inner-core side to ZB toward the outer-shell surface is observed. Overall, we propose that the WZ polytype in the GaAs NWs decreases because of the strain induced by the growth of the GaNAs shell with a smaller lattice constant.